Identification and functional characterization of ABCA4 gene variants in three patients with Stargardt disease or retinitis pigmentosa - Luo, Qi; Huang, Juan; Shi, Lu; Zhang, Guanghong; Xue, Linping; Wu, Kehu; Li, Xiaoyu; Yang, Lei; Li, Dujun; Mao, Liangwei; Luo, Jihong (Frontiers in Genetics, 2025)
IntroductionThe diversity of phenotypes, ranging from inherited retinal dystrophies (such as Stargardt disease 1, cone–rod dystrophy 3, and retinitis pigmentosa 19) to late-onset age-related macular degeneration 2, has been attributed to loss-of-function variants in the ABCA4 gene. In this study, we aimed to identify and analyze potential pathogenic ABCA4 variants in patients with Stargardt disease or retinitis pigmentosa and to explore the impact of an intronic variant (NM_000350.3:c.6386 + 4A>G) on mRNA splicing.MethodsWe enrolled three patients from unrelated families with Stargardt disease or retinitis pigmentosa after comprehensive ophthalmological evaluations were performed. Whole-exome sequencing and Sanger sequencing were applied for mutation screening, focusing on inherited retinal dystrophy-related genes. Additionally, the splicing alteration caused by c.6386 + 4A>G was functionally characterized by a minigene splicing assay.ResultsFive ABCA4 germline variants were detected in three patients: one frameshift, one nonsense, one splicing, and two missense variants. Furthermore, two pathogenic and two likely pathogenic variants and one variant of uncertain significance were determined according to ACMG/AMP and ClinGen sequence variant interpretation (SVI) guidelines. The minigene splicing assay result proved that c.6386 + 4A>G affected the wild-type donor splice-site recognition of intron 46 and yielded a truncated transcript with a 47-bp deletion in exon 46.DiscussionOur study identified two novel ABCA4 variants, expanding the mutational spectrum of the ABCA4 gene in Stargardt disease and retinitis pigmentosa while providing new insights into the molecular pathology of ABCA4 splicing defects.